SHEAR STRESS DURING EARLY EMBRYONIC STEM CELL DIFFERENTIATION PROMOTES HEMATOPOIETIC AND ENDOTHELIAL PHENOTYPES - Wolfe, Russell P. (2013)
Pluripotent embryonic stem cells (ESCs) are a potential source for cell-based tissue engineering and regenerative medicine applications, but their translation into clinical use will require efficient and robust methods for promoting differentiation. Fluid shear stress, which can be readily incorporated into scalable bioreactors, may be one solution for promoting endothelial and hematopoietic phenotypes from ESCs. Here we applied laminar shear stress to differentiating ESCs using a 2D adherent parallel plate configuration to systematically investigate the effects of several mechanical parameters. Treatment similarly promoted endothelial and hematopoietic differentiation for shear stress magnitudes ranging from 1.5 to 15 dyne/cm(2) and for cells seeded on collagen-, fibronectin-, or laminin-coated surfaces. Extension of the treatment duration consistently induced an endothelial response, but application at later stages of differentiation was less effective at promoting hematopoietic phenotypes. Furthermore, inhibition of the FLK1 protein (a VEGF receptor) neutralized the effects of shear stress, implicating the membrane protein as a critical mediator of both endothelial and hematopoietic differentiation by applied shear. Using a systematic approach, studies such as these help elucidate the mechanisms involved in force-mediated stem cell differentiation and inform scalable bioprocesses for cellular therapies.